Kewenangan Unit Tipikor Polres Seram Bagian Barat Terhadap Penyidikan dan Penuntutan Tindak Pidana Korupsi Dalam Rangka Penegakan Hukum - Putra, Aprilianto Pratama; Saptenno, Marthinus Johanes; Hehanussa, Deassy Jacomina Anthoneta (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2024)
Introduction: Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, the criminal act of corruption not only harms state finances, but violates the social and economic rights of the community at large. Institutions that include law enforcement are the National Police, KPK, and the Prosecutor's Office. Among the three institutions, the National Police, in this case, the West Seram Police Investigation Unit (SBB) is an experienced institution in investigating various cases of its jurisdiction. Article 1 father (1) of the Code of Criminal Procedure An investigator is an official of the national police of the Republic of Indonesia or certain civil servant officials who are specially authorized by law to conduct investigations. While the prosecutor's office has the same duties and authorities in eradicating corruption specifically the Attorney General by Law Number 16 of 2004 also regulates the duties and authorities of the Attorney General, namely Articles 35, 36, 37 of Law Number 16 of 2 Purposes of the Research: Review and discuss the authority of the West Seram Police Corruption Unit (SBB) regarding Investigation and Prosecution in the context of law enforcement. Examine and discuss any inhibiting factors influencing the authority of the West Seram Police Corruption Unit (SBB) regarding the investigation and prosecution of criminal acts of corruption in the context of law enforcement Methods of the Research: The research method used is normative juridical Results of the Research: Certain civil servant officials who are specially authorized by law to conduct investigations. While the prosecutor's office has the same duties and authorities in eradicating corruption specifically the Attorney General by Law Number 16 of 2004 also regulates the duties and authorities of the Attorney General, namely Articles 35, 36, 37 of Law Number 16 of 2.